AN ANALYSIS OF DEIXIS TYPES AND ITS’ REFERENCE IN “CINDERELLA” MOVIE - Kadek Ari Widianti; Ni Luh Nyoman Seri Malini; Nissa Puspitaning Adni (STKIP Siliwangi, 2024)
The study aims to identify deixis types and their references in